HAK CIPTA SEBAGAI SUATU OBJEK JAMINAN FIDUSIA (Faculty of Law, University of Dr. Soetomo, 2018)
Copyright is the exclusive right of the creator that arise automatically based on the principle of declarative after an invention is embodied in a tangible form without prejudice to the restrictions in accordance with the provisions of the legislation. Copyright can be used as the object of fiduciary cause it has an economic value. Creditors are willing to give the debt to the debtor, if debtor can provide wealth to ensure smooth payment of debts. The object of fiduciary is not controlled by the creditor, but remains dominated by the debtor. There is no physical delivery of goods, only the economic rights of copyright can be transferred. Copyright may be encumbered by fiduciary guarantee provided that the encumbrance be put not over the copyrighted work, but on its economic value. In order to be secured under fiduciary claim, copyright must be registered with the Cirectorate General of Intellectual Property Rights